Massage Therapy for Infants and Toddlers With Acute Respiratory Infections: A Literature Review - Agussalim, Asrawaty; Kusmiyati, Yuni; Mashoedi, Imam Djamaluddin (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Acute respiratory infection (ARI) is a health problem that causes morbidity and mortality in Indonesia. This infectious disease most often affects infants and toddlers . Massage therapy that aims to relax and overcome various health problems in infants and toddlers. Massage therapy is the initial treatment of minor ailments such as coughs, colds, and lack of appetite. This literature review aims to analyze the benefits of massage therapy in ISPA infants. The research method used by the author is a literature review using a database through Pubmed, Science Direct, Ebsco, and Google Scholar from 2009 to 2019 This article discusses massage therapy in ARI infants with upper respiratory infections and lower respiratory tract infections. Literature search results show that massage therapy provides recovery benefits for ARI symptoms such as overcoming fever, overcoming sleep difficulties, improving the immune system, improving the work of the respiratory system, blood circulation, increasing concentration etc.